For twice in my life - Christie, Annette (Little Brown and Company, 2023)
A second try at love becomes more than one woman bargained for in this delightfully funny and romantic new novel from the author of The Rehearsals. Can one little lie lead to a big second chance? Layla's chaotic life transformed when she met Ian Barnett. Ambitious, committed, and thoughtful, Ian has been everything she'd dreamed of, and she knows he'd say the same of her. So when he breaks up with her out of the blue, Layla is stunned. What went wrong? But then, Layla gets a call from the local hospital. Ian's had a biking accident. He's okay, but he needs someone--his someone--to get him home safely. As it becomes clear Ian doesn't remember he ended things, it also becomes clear that the accident has given him a new outlook on life...and Layla a second chance to get things right. That is, until Ian's younger brother comes to town. Matt is restless, unpredictable, and threatens to upset the careful balance Layla and Ian have rebuilt. As things get more complicated both at home and at work, Layla realizes she might lose her chance at real love--and real happiness--if she doesn't come clean about the stories she's been telling: to Ian, to Matt, to her family, and most importantly, to herself.